Strategi Promosi oleh Rumah Kurasi dalam Meningkatkan Penjualan yang Efektif melalui Platform TikTok - Dewi Ayu Intan Lestari; Sutantri Sutantri; Iva Khoiril Mala (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to find out what strategies are carried out by the Rumah Kurasi in increasing effective sales through the TikTok platform. The method used in this study is with a qualitative descriptive approach, this research is a field research and the data used in this study are primary and secondary data, with data collection techniques through observation and interviews. The results showed that various TikTok features can make it easier for the Rumah Kurasi to create interesting content so that it can increase the audience. The large audience of content is very helpful for the Rumah Kurasi in marketing its products. Sales promotion through curated product reviews through live TikTok can increase effective sales.